2019
DOI: 10.1002/nbm.4116
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of quantitative MRI metrics with myelin basic protein (MBP) staining in a murine model of demyelination

Abstract: Myelin imaging in the central nervous system is essential for monitoring pathologies involving white matter alterations. Various quantitative MRI protocols relying on the modeling of the interactions of water protons with myelinated tissues have shown sensitivities in case of myelin disruption. Some extracted model parameters are more sensitive to demyelination, such as the bound pool fraction (f) in quantitative magnetization transfer imaging (qMTI), the radial diffusivity in diffusion tensor imaging (DTI), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 62 publications
(141 reference statements)
2
21
0
Order By: Relevance
“…MPF values measured in WM and GM regions in this study are in average similar to those reported by Ou et al 17 (recalculated from the pool size ratio), Thiessen et al, 13 and by our group 14 in paraformaldehyde‐fixed mouse brains. Values were somewhat lower than those estimated by Khodanovich et al 23 in in vivo mice at 11.7T, although precise constrained parameters were not provided.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…MPF values measured in WM and GM regions in this study are in average similar to those reported by Ou et al 17 (recalculated from the pool size ratio), Thiessen et al, 13 and by our group 14 in paraformaldehyde‐fixed mouse brains. Values were somewhat lower than those estimated by Khodanovich et al 23 in in vivo mice at 11.7T, although precise constrained parameters were not provided.…”
Section: Discussionsupporting
confidence: 90%
“…32,33 Fields of view (FOV) were tilted so that their respective edge was parallel to the corpus callosum along the genusplenium line determined on a 2D T 2 -weighted sagittal scan, thus mitigating potential partial volume effects. 14 All native images were denoised using BM4D 34 (exemplified in Supporting Information Figure S1, which is available online) and rigidly registered onto the 10-degrees volume of the T 1 mapping protocol using ANTs. 35 Brain extraction was manually performed using ITK-SNAP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Postmortem formalin‐fixed brains showed significant changes in the MT ratio (MTR), which weakened the association between MT effects and myelin content 11 . A postmortem MWI study also showed that the T 2 distribution can be altered, probably because of myelin sheath loosening, cell shrinkage, and changes in various water compartments during the fixation process 12,13 …”
Section: Introductionmentioning
confidence: 99%